2007
DOI: 10.1088/1748-9326/2/4/044002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effective reduction of fine primary particulate matter emissions in Finland

Abstract: Policies to reduce adverse health impacts of fine particulate matter (PM 2.5 ) require information on costs of abatement and associated costs. This paper explores the potential for cost-efficient control of anthropogenic primary PM 2.5 emissions in Finland. Based on a Kyoto-compliant energy projection, two emission control scenarios for 2020 were developed. 'Baseline' assumes implementation of PM controls in compliance with existing legislation. 'Reduction' assumes ambitious further reductions. Emissions for 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…. Of course, future efforts to mitigate PM 2.5 and health consequences will be more difficult and more costly since relatively “easy” tasks have been accomplished . For example, a clean heating campaign covered the flattest terrain with high population density in the R28 region.…”
Section: Discussionmentioning
confidence: 99%
“…. Of course, future efforts to mitigate PM 2.5 and health consequences will be more difficult and more costly since relatively “easy” tasks have been accomplished . For example, a clean heating campaign covered the flattest terrain with high population density in the R28 region.…”
Section: Discussionmentioning
confidence: 99%
“…Due to rising oil prices in the past years and attempts to reduce greenhouse gas emissions, many communities have shifted from fossil fuels to renewable biomass fuels. Without corresponding changes in emission regulations, this shift could lead to a considerable increase in the ambient air fine particle concentrations, since small-scale biomass combustion has been found to emit high amounts of fine particles. , Moreover, increased particle concentrations in the ambient air have been found to correlate with adverse health effects, including respiratory and cardiovascular illnesses as well as increased mortality . Further, it has been observed that in the case of combustion-related particles, the fine particle fraction (PM1 or PM2.5) is especially harmful to human health .…”
Section: Introductionmentioning
confidence: 99%
“…2009) and RAINS/GAINS-Netherlands (Van Jaarsveld 2004). Another national level implementation is the FRES model (Karvosenoja et al 2007), developed at the Finnish Environment Institute (SYKE) to assess, in a consistent framework, the emissions of air pollutants, their processes and dispersion in the atmosphere, effects on the environment and potential for their control and related costs. An additional important initiative at national level is the PAREST project, in which emission reference scenarios until 2020 were constructed for PM and for aerosol precursors, for Germany and Europe (Builtjes et al 2010).…”
Section: Available Toolsmentioning
confidence: 99%